Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1984
DOI: 10.1073/pnas.81.11.3552
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni egg granuloma size reduction in challenged baboons after vaccination with irradiated cryopreserved schistosomula.

Abstract: Young male baboons born in captivity were immunized with ad attenuated, cryopreserved schistosomular vaccine derived from V-irradiated (50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…Schistosome eggs and their secreted products provide a continuous antigenic stimulus for the immune response. If these antigens are not sequestered or neutralized effectively, they can damage the affected tissues, with hepatocytes being particularly sensitive to toxins secreted by the eggs 3 . Indeed, T‐cell‐deprived, nude, severe combined immunodeficiency disease or egg‐tolerized mice all die earlier than comparably infected immunologically intact mice because they are unable to mount a protective granulomatous response.…”
Section: ‘The Good and The Bad’ Features Of Granulomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Schistosome eggs and their secreted products provide a continuous antigenic stimulus for the immune response. If these antigens are not sequestered or neutralized effectively, they can damage the affected tissues, with hepatocytes being particularly sensitive to toxins secreted by the eggs 3 . Indeed, T‐cell‐deprived, nude, severe combined immunodeficiency disease or egg‐tolerized mice all die earlier than comparably infected immunologically intact mice because they are unable to mount a protective granulomatous response.…”
Section: ‘The Good and The Bad’ Features Of Granulomasmentioning
confidence: 99%
“…If these antigens are not sequestered or neutralized effectively, they can damage the affected tissues, with hepatocytes being particularly sensitive to toxins secreted by the eggs. 3 Indeed, T-cell-deprived, nude, severe combined immunodeficiency disease or egg-tolerized mice all die earlier than comparably infected immunologically intact mice because they are unable to mount a protective granulomatous response. Widespread hepatic damage induced by toxic egg products contributes to the decreased survival of infected immunocompromised mice.…”
mentioning
confidence: 99%
“…Most previous attempts at protection using irradiated larvae (Taylor, M.G. et al 1976, Damian et al 1984, James, E. et al 1986) have been disappointing. However one trial reported a decrease in both worm burden and faecal egg counts after immunization with gammaattenuated Schistosoma mansonicercariae (Stek et al 198 1).…”
Section: Introductionmentioning
confidence: 99%
“…Eggs trapped in the hepatic microvasculature induce the formation of granulomas. However, with time, infected individuals can modulate the granulomas and become relatively immune to reinfection by the process of concomitant immunity (Damian et al 1974(Damian et al , 1984. To be voided, Schistosoma mansoni eggs must penetrate the walls of the intestines.…”
Section: Discussionmentioning
confidence: 99%